Reversible Mixed Dynamics: A Concept and Examples - Gonchenko, S.V. (Discontinuity, Nonlinearity, and Complexity, 2026)
We observe some recent results related to the new type of dynamical chaos, the so-called, “mixed dynamics” which can be considered as an intermediate link between “strange attractor“ and “conservative chaos”. We propose a mathematical concept of mixed dynamics for two-dimensional reversible maps and consider several examples.